Certain aspects of recidivism in criminal law and criminology - Mijalčić Jelena (Glasnik Advokatske komore Vojvodine)
This paper delves into the analysis of certain criminal law and criminological aspects of recidivism. The author examines the factors that most frequently lead to the occurrence of recidivism, as well as the different personality types of repeat offenders. The paper highlights the most significant forms of recidivism as well as the criminal law implications of each type. Based on this analysis, the author proposes ideas on how recidivism could be minimized within a social system.